Effect of Oxygen Plasma on Sprout and Root Growth, Surface Morphology and Yield of Garlic - Holc, Matej (Plants (Basel), 2019)
Depending on the climate, garlic can be planted either in the fall or spring for a harvest in the summer, but spring planting might require the strengthening of the plant by external techniques. We have used low pressure, inductively coupled, radio frequency oxygen plasma for the treatment of peeled garlic cloves of a spring-planted Slovenian autochthonous cultivar. The aim of the study was to assess the effects of plasma treatment on garlic clove shoot and root growth and, ultimately, the yield. The roles of surface chemistry, surface morphology, and water uptake in these effects were also evaluated. The plasma treatment of cloves induced increases in water uptake. The increases were explained by changes in surface morphology that were determined by using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Nanostructured epicuticular wax structures appeared at the cuticle surface. The optimal treatment parameters accelerated root growth, but not shoot growth, in a laboratory setting. After growth in the field, the trends indicated that plant height and dried bulb mass increase, but the improvements were not statistically significant.